Niektóre prawnokarne (represyjne) metody przeciwdziałania alkoholizmowi i narkotykom, w tym zwłaszcza tak zwanym dopalaczom, przez gminy - Jóźwiak, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The role of territorial self-government in alcoholism and drug control is significant. Municipalities have the widest competence in this sphere. Among the many different rights granted to municipalities, one can distinguish those of a prophylactic, preventive, but also criminal (repressive) nature. The latter are the subject of this article. The role of territorial self-government is not — as a rule — the use of repressive measures, but sometimes they are extremely effective in fighting against such negative phenomena as alcoholism or drug addiction. That is why the article proposes introducing solutions of a criminal nature, which are to help municipalities fight against designer drugs.
Keywords: alkoholizm; narkotyki; dopalacze; charakter represyjny